LGBT DALAM PERSPEKTIF AGAMA DAN HAM - Masthuriyah Sa’dan (Nizham Jurnal Studi Keislaman, 2016)
The decision of “haram” which is coming from The Indonesian Islamic Scholar Council (MUI ) against such a group which has homo sexual oriented and the death penalty for sexual offenders "deviant" make the people of Indonesia shaken, especially those who feel they have gender identity "third". "Religion" which should give way ease, as if to bury alive a person who has a gay sexual orientation. In fact, legal instruments, regional, national and international human rights recognize their rights as human beings. By using contemporary humanities social approach, this paper presents the Lesbian, Gay, Bisexual And Transgender group as a human's dignity to be treated like a human being which must be respected.